2018
DOI: 10.1186/s12918-018-0595-5
|View full text |Cite
|
Sign up to set email alerts
|

Landscape reveals critical network structures for sharpening gene expression boundaries

Abstract: BackgroundSpatial pattern formation is a critical issue in developmental biology. Gene expression boundary sharpening has been observed from both experiments and modeling simulations. However, the mechanism to determine the sharpness of the boundary is not fully elucidated.ResultsWe investigated the boundary sharpening resulted by three biological motifs, interacting with morphogens, and uncovered their probabilistic landscapes. The landscape view, along with calculated average switching time between attractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Our study suggests that different patterns of morphogenetic changes observed in the explants exposed to different FGFs is due to changes in the position of the boundary between proliferating and differentiating parts of the epithelial explant. The boundary position is determined by the decrease/loss of ERK1/2 activation between the “stalks” and “buds.” Similar concept of boundaries between gene expression domains could be implied to different tissues and is central to many developmental processes (Cottrell et al, 2012; Caggiano et al, 2017; Neijts and Deschamps, 2017; Li et al, 2018). For example Sawada and coauthors (Sawada et al, 2001) showed that FGF/MAPK signaling is a crucial positional cue in somite boundary formation.…”
Section: Discussionmentioning
confidence: 93%
“…Our study suggests that different patterns of morphogenetic changes observed in the explants exposed to different FGFs is due to changes in the position of the boundary between proliferating and differentiating parts of the epithelial explant. The boundary position is determined by the decrease/loss of ERK1/2 activation between the “stalks” and “buds.” Similar concept of boundaries between gene expression domains could be implied to different tissues and is central to many developmental processes (Cottrell et al, 2012; Caggiano et al, 2017; Neijts and Deschamps, 2017; Li et al, 2018). For example Sawada and coauthors (Sawada et al, 2001) showed that FGF/MAPK signaling is a crucial positional cue in somite boundary formation.…”
Section: Discussionmentioning
confidence: 93%
“…Many theoretical works have devoted to study the boundary sharpening process. By utilizing energy landscape, functions of each gene regulation in this system were demonstrated [86]. Also an increase level of noise allows switching more rapidly, but increases the rate of spontaneous switching and thereby decreases the precision of gene expression boundary [87].…”
Section: Utilizing Gene Expression Noise To Battle Noise In Morphogenmentioning
confidence: 99%
“…In the model ( Serbanescu et al., 2020 ), it has observed that cell size variability depends on the balance between ribosomes and division protein which depends on nutrient availability. Gene expression boundary sharpening controlled by morphogens shows that mutual repressed self-activation network is more robust than others against parameter perturbation ( Li et al., 2018 ). A noise-driven cell differentiation model ( Safdari et al., 2020 ) that uses a GRN with two mutually inhibiting transcription factors shows an increasing number of differentiated cells as division plane deviate from center of the cell.…”
Section: Introductionmentioning
confidence: 99%